Enhancing High School Students' Understanding of the Excretory System through Problem-Based Learning - Dhea Febria; Aswinda Aswinda; Septia Yuliadip; Fulsiana Yustia; Kharisma Dwi Khorneliana; Jodion Siburian; Ine Tentia (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Low cognitive learning outcomes in biology on the excretory system are often due to conventional learning methods that make students passive and focus on memorization. This study aims to improve students' cognitive learning outcomes by applying the Problem-Based Learning (PBL) model. The study used the Classroom Action Research (CAR) method, conducted in two cycles with 24 students from SMA Negeri 1 Kota Jambi. Data were collected through pretests and posttests in each cycle and analyzed using descriptive statistics, including average scores and learning completeness percentages. The results showed an increase in the average score from 46.25 in the pre-cycle to 80.83 in cycle I and 87.08 in cycle II, with the mastery percentage increasing from 4.17% to 100%. These findings indicate that the PBL model is effective in improving cognitive learning outcomes and fostering students' conceptual understanding and critical thinking skills. This study contributes by showing that the application of PBL through classroom action research can be an effective learning strategy for improving the quality of biology learning in secondary schools.